(untitled) (Anuário Antropológico, 2023)
The Zika virus (ZV) arrived in Brazil as a new epidemic between the years of 2015 and 2016. Its main consequence was reproductive, with the birth of more than 4,000 children with what was called the Congenital Zika Virus Syndrome (CZVS), a complex set of disabilities that requires a range of specialized care. So far, in the anthropological literature, much has been said about these disabilities, about the daily care and rights of these children and their families, but not so much has been documented about the relationship they had with science that tried to understand this new virus, this new syndrome. The article discusses why this specific population accepted the invitations coming from science and their critical reflections on this intense interaction with science. Based on a collective and ethnographic along four years of research in Recife/PE, the epicenter of the ZV epidemic, the article intends to contribute to an Anthropology of science less “internal to the laboratory”, since the research subjects involved in the production of knowledge about the ZV and CZVS also helped to assess and – most importantly – construct this science.